Digital Engagement of Older Adults in Lithuania: Obstacles and Support Opportunities - Gedvilaitė-Kordušienė, Margarita; Rapolienė, Gražina (Socialinė teorija, empirija, politika ir praktika, 2023)
While Lithuania advances rapidly in the ICT sector, a digital divide persists among older adults. A study of 289 elderly Internet users highlighted key barriers and facilitators in digital engagement. Motivation stemmed from personal qualities like curiosity and past work experience with digital tools. Major barriers included language challenges, technical jargon, limited support, device comprehension issues, and emotional factors. Formal and informal training, peer support, gaming‘s role, and family, particularly younger members, emerged as crucial learning aids. The study underscores the need for strategies tailored to enhance digital inclusion of older people in Lithuania.
Keywords: digital inclusion; older adults; barriers and facilitators of digital inclusion